FAKTOR DOMINAN MEMPENGARUHI INFLASI DI INDONESIA - Syaipan Djambak (Department of Development Economics, Universitas Sriwijaya, 2008)
Inflation is a macro-economic disease that can damage the economy joints , damage the climate in production, and weaken purchasing of community. Because such damage to the economy as a result of high inflation, the monetary authority always tried to recruit all of the potential for inflation to avoid a major. Throughout history of Indonesian economy until the end of the year 2006, the average inflation rate (over 27 years) reached 11.03% of the inflation level is high enough, even 1966 years old indonesia inflation reached 650% and inflation reached 120% in 1967, and inflation in 1998 reached 77.63%.Based on existing conditions in inflation, the formulation of the problem examined in this research is: